The Effect of the Educaplay Assisted Learning Problem Based Learning Model on Students' Mathematical Problem-Solving Ability in SPLDV Class X Material of SMA Negeri 1 Medan - Angelica Sigalingging; Aprilia Windasari; Dinda Alexa Nabila Utomo; Jeremy Akbar Vivaldy; Laura Yohana Sianturi; Ronauli Simamora (Jurnal Multidisiplin Teknologi dan Arsitektur, 2026)
This study aims to determine the effect of the application of the Problem Based Learning (PBL) model assisted by Educaplay media on students' mathematical problem-solving ability in the Two-Variable Linear Equation System (SPLDV) material. This study uses a quantitative approach with the experimental method and the One Group Pretest-Posttest design. The subject of the study is 30 students. The instrument used is a mathematical problem-solving ability test in the form of description questions. The data were analyzed using the Shapiro-Wilk normality test, the paired sample t-test, the Wilcoxon test, and the N-Gain analysis. The results showed that there was an increase in the average score from the pretest of 41.7 to 67.1 in the posttest. The results of the hypothesis test showed a significant difference between the pretest and the posttest (p < 0.001) with an effect size value of 4.55 which is in the very large category. Thus, it can be concluded that the Educaplay-assisted PBL model has a significant and effective effect in improving students' mathematical problem-solving skills.